Internal and External Determinants of Corporate Social Responsibility Practices in Multinational Enterprise Subsidiaries in Developing Countries: Evidence from Ethiopia - Gulema, Tolossa Fufa; Roba, Yadessa Tadesse (Journal of Asian Business Strategy, 2020)
This research attempts to investigate internal drivers and external determinants of CSR strategies practiced by MNC’s using Institutional theory and the resource-based view, we integrate internal motives and external factors, that MNCs business orientations and political behaviors are highly related to firms’ CSR practices selection as internal and external determinants, respectively. We find that firms who are oriented to raise competitiveness with collaborative attitudes against host governments seek more exploring corporate social responsibility practices. On the other hand, firms’ local orientation that is to build legitimacy with accommodative attitudes toward host governments has positive relations with exploiting CSR practices. We employed a multiple regression analysis survey data collected from MNC subsidiaries operating in Ethiopia. While most of the assumptions were supported, we collect an interesting result that exploiting CSR practices are positively related to both orientations, which implies that traditional CSR practices are treated fundamentally of importance in developing countries.